PENEGAKAN HUKUM TERHADAP KAPAL TANKER FREYA BERDASARKAN KONVENSI HUKUM LAUT 1982 - Dhimas Prima Thufeil; Anto Ismu Budianto (Faculty of Law, Universitas Trisakti, 2023)
Foreign ships have the right of innocent passage and the right of transit passage through the territorial waters of an archipelagic state. This is regulated in the 1982 Law of the Sea Convention. The foreign tanker MT Freya, entered the Indonesian EEZ, traded oil illegally and polluted the environment. The formulation of the problem in this thesis is whether the entry of MT Freya into Indonesia's EEZ in Batam waters is contrary to the 1982 Sea Law Convention and how to proceed with the law against foreign ships that do not comply with the 1982 Sea Law Convention. The research method used is normative legal research, data collection through literature studies, qualitative data analysis using deductive methods and secondary data collection. The results of the research, discussion, and conclusions are: the MT Freya tanker has violated the 1982 Law of the Sea Convention concerning innocent passage rights, transit passage rights, and also regarding dumping.